KEDUDUKAN MAHKAMAH INTERNASIONAL DALAM MENGADILI PERKARA KEJAHATAN KEMANUSIAAN - Rubiyanto Rubiyanto (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2018)
The main matter, a case can be investigated trial by International court of justice is human right violence for instance genocide, war, ethnic killing, human trafficking and salve. No all legal action or law suit could be submitted to International court. Based on the background, could be inferred : How about the existence of International court of justice to take trial human crime ? The matter could be conclude that International court of justice one of United Nation organ which have the main task to solve the International dispute, human crime and human right violence in a country.